2008
DOI: 10.5194/cp-4-1-2008
|View full text |Cite
|
Sign up to set email alerts
|

Changes in C<sub>3</sub>/C<sub>4</sub> vegetation in the continental interior of the Central Himalayas associated with monsoonal paleoclimatic changes during the last 600 kyr

Abstract: Abstract.A continuous lacustrine sediment core obtained from the Kathmandu Valley in the Central Himalayas revealed that cyclical changes in C 3 /C 4 vegetation corresponded to global glacial-interglacial cycles from marine isotope stages (MIS) 15 to MIS 4. The C 3 /C 4 vegetation shifts were reconstructed from significant changes in the δ 13 C values of bulk organic carbon. Glacial ages were characterized by significant 13 C enrichment, due to the expansion of C 4 plants, attributed to an intensification of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…As a result, changes of various kind of proxy during the last 600 kyr were reconstructed: history of vegetation and monsoon climate (Fujii et al 2004a;Maki et al 2004), ecological changes of diatom (Hayashi et al 2009), and changes in TOC, C/N, δ 13 C of organic matter (Mampuku et al 2008). Mineralogical study of lacustrine clay during the last glacial period revealed that amount of clay fraction, clay mineral assemblage, and crystallinity were strongly controlled by paleoclimate (Kuwahara et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, changes of various kind of proxy during the last 600 kyr were reconstructed: history of vegetation and monsoon climate (Fujii et al 2004a;Maki et al 2004), ecological changes of diatom (Hayashi et al 2009), and changes in TOC, C/N, δ 13 C of organic matter (Mampuku et al 2008). Mineralogical study of lacustrine clay during the last glacial period revealed that amount of clay fraction, clay mineral assemblage, and crystallinity were strongly controlled by paleoclimate (Kuwahara et al 2010).…”
Section: Introductionmentioning
confidence: 99%